2019
DOI: 10.1158/1541-7786.mcr-18-1231
|View full text |Cite
|
Sign up to set email alerts
|

The Pioneering Role of GATA2 in Androgen Receptor Variant Regulation Is Controlled by Bromodomain and Extraterminal Proteins in Castrate-Resistant Prostate Cancer

Abstract: The androgen receptor (AR) is a key driver of prostate cancer development. Antiandrogens effectively inactivate the AR, but subsequent AR reactivation progresses the disease to castrate-resistant prostate cancer (CRPC). Constitutively active AR splice variants (AR-V) that function unchallenged by current AR-targeted therapies are key drivers of CRPC. Currently, very little is known about the regulation of AR-Vs at the chromatin level. Here, we show that the pioneer factor GATA2 is a critical regulator of AR-Vs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
(92 reference statements)
0
19
0
Order By: Relevance
“…Interestingly, the GATA2 cistrome shares a consistent overlap with bromodomain and extra terminal (BET) proteins and is codependent for DNA binding; in line with this observation, BET inhibitors compromise GATA2 activity in CRPC cells [292]. These observations support the use of BET inhibitors in CRPC patients overexpressing GATA2 [292].…”
Section: Novel Therapies For Prostate Cancermentioning
confidence: 79%
See 2 more Smart Citations
“…Interestingly, the GATA2 cistrome shares a consistent overlap with bromodomain and extra terminal (BET) proteins and is codependent for DNA binding; in line with this observation, BET inhibitors compromise GATA2 activity in CRPC cells [292]. These observations support the use of BET inhibitors in CRPC patients overexpressing GATA2 [292].…”
Section: Novel Therapies For Prostate Cancermentioning
confidence: 79%
“…The study of AR-variant transcriptome is in part dependent upon FOXA1 [655]. A recent study showed that GATA2 is a critical regulator of AR-Vs [292]. Interestingly, the GATA2 cistrome shares a consistent overlap with bromodomain and extra terminal (BET) proteins and is codependent for DNA binding; in line with this observation, BET inhibitors compromise GATA2 activity in CRPC cells [292].…”
Section: Novel Therapies For Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, GATA2 directly promotes the expression of the AR before and after androgen stimulation . In cell lines derived from an aggressive, castrate‐resistant (antiandrogen‐resistant) prostate cancer, GATA2 is a critical regulator of the transcriptional activity of a constitutively active AR variant; an interaction with BET proteins facilitates GATA2 chromatin occupancy and promotes the expression of cell‐cycle‐related genes targeted by GATA2 and regulated by the AR variant—thus favoring cell proliferation and disease progression …”
Section: Gata2mentioning
confidence: 99%
“…Many previous studies have attempted to find target molecules for CRPC therapy. GATA2 (GATA-binding protein 2) and FOXA1 (forkhead box A1) have been proposed as important regulators of AR splice variant-driven transactivation that has been shown to be associated with CRPC [ 5 ]. GATA2 induces tumorigenicity and resistance to chemotherapy by giving rise to the GATA2–IGF2 (insulin like growth factor 2) axis in CRPC [ 6 ].…”
Section: Introductionmentioning
confidence: 99%